Clustered Regularly Interspaced Short Palindromic Repeats Genotyping of Multidrug-Resistant Salmonella Heidelberg Strains Isolated From the Poultry Production Chain Across Brazil - Monte, Daniel F. M. [UNESP]; Nethery, Matthew A.; Berman, Hanna; Keelara, Shivaramu; Lincopan, Nilton; Fedorka-Cray, Paula J.; Barrangou, Rodolphe; Landgraf, Mariza (Frontiers, 2022)
Salmonella enterica subsp. enterica serovar Heidelberg has been associated with a broad host range, such as poultry, dairy calves, swine, wild birds, environment, and humans. The continuous evolution of S. Heidelberg raises a public health concern since there is a global dispersal of lineages harboring a wide resistome and virulome on a global scale. Here, we characterized the resistome, phylogenetic structure and clustered regularly interspaced short palindromic repeats (CRISPR) array composition of 81 S. Heidelberg strains isolated from broiler farms (n = 16), transport and lairage (n = 5), slaughterhouse (n = 22), and retail market (n = 38) of the poultry production chain in Brazil, between 2015 and 2016 using high-resolution approaches including whole-genome sequencing (WGS) and WGS-derived CRISPR genotyping. More than 91% of the S. Heidelberg strains were multidrug-resistant. The total antimicrobial resistance (AMR) gene abundances did not vary significantly across regions and sources suggesting the widespread distribution of antibiotic-resistant strains from farm to market. The highest AMR gene abundance was observed for fosA7, aac(6′)-Iaa, sul2, tet(A), gyrA, and parC for 100% of the isolates, followed by 88.8% for blaCMY–2. The β-lactam resistance was essentially driven by the presence of the plasmid-mediated AmpC (pAmpC) blaCMY–2 gene, given the isolates which did not carry this gene were susceptible to cefoxitin (FOX). Most S. Heidelberg strains were classified within international lineages, which were phylogenetically nested with Salmonella strains from European countries; while CRISPR genotyping analysis revealed that the spacer content was overall highly conserved, but distributed into 13 distinct groups. In summary, our findings underscore the potential role of S. Heidelberg as a key pathogen disseminated from farm to fork in Brazil and reinforce the importance of CRISPR-based genotyping for salmonellae. Hence, we emphasized the need for continuous mitigation programs to monitor the dissemination of this high-priority pathogen.
Keywords: antibiotic resistance; CRISPR; foodborne disease; phylogeny; Salmonella Heidelberg; WGS